"Let´s Party!" Harry Potter fan fiction sites as social settings for narrative gender constructions. (5th June 2014) - Karlsson, Marie; Olin-Scheller, Christina
Abstract : Online communication is often presented in research as offering ways for young people to explore various forms of masculinity and femininity, which, in turn, could extend the notions of gendered identity. This paper explores how a Harry Potter fan fiction website can function as an online setting for gender identity construction among young fans. A positioning analysis of a small story told in an Internet Relay Chat (IRC) shows that although traditional gendered subject positions are explored and troubled in the story and its telling, heteronormativity prevails through the interpretative repertoires made available by the textual universe of Harry Potter. On the other hand, the positioning analysis of the small story activates an understanding of the interplay between the relational order among story characters and among the storytellers that can be seen as opening up a space between what is the told and the telling that allows the fans to experiment with aspects of gender identities that are related to power and control within an interpretative repertoire of heteronormativity.